(untitled) (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2023)
This study presents a comparative analysis of postcolonial identity as portrayed in African and South Asian English literature, examining how writers from both regions negotiate themes of cultural hybridity, displacement, resistance, and self-definition in the aftermath of colonial rule. Drawing on the works of authors such as Chinua Achebe, Ngũgĩ wa Thiong'o, Salman Rushdie, and Arundhati Roy, the research explores how historical, linguistic, and socio-political contexts shape literary expressions of identity. While African literature often grapples with reclaiming indigenous voices and confronting neocolonial power structures, South Asian literature tends to emphasize fragmented identities and the negotiation between tradition and modernity. The analysis highlights both convergences and divergences in narrative strategies, language use, and the representation of nationhood, ultimately revealing the complex and evolving nature of postcolonial identity in English-language literary traditions. This comparative approach underscores the importance of regional specificities while recognizing shared struggles across postcolonial societies.